Phenomenology After Deconstruction: "Voice and Phenomenon" as a Prolegomenon to Husserl’s Genetic Method - Zihao LIU (Studia Universitatis Babeș-Bolyai. Philosophia, 2023)
Reading Voice and Phenomenon from a phenomenological perspective, this paper argues that the book is an internal criticism of Husserlian phenomenology that, among other things, can serve as an introduction to Husserl’s genetic method. Derrida’s most powerful arguments are delivered by turning the Cartesian method of Logical Investigations and Ideas I to Husserl’s inquiries into time-consciousness; as such, it is a phenomenological criticism through and through. An analysis of Husserl’s later manuscripts and lectures published posthumously shows that driven by what Derrida calls the radicality of intuitionism, Husserl has developed a genetic phenomenological method that breaks free from the metaphysics of presence and arrived at a conception of meaning and language that is similar to Derrida’s.